PELATIHAN PENGGUNAAN KOMPOR BIOMASSA GUNA MENINGKATKAN PRODUKTIFITAS PEDANGGANG GORENGAN - Arif Setyo Nugroho; Didik Achadi W; Y Yulianto Kristianto (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of community service is carried out by providing solutions for fried food traders who sometimes experience problems, especially regarding the process of making merchandise for sale. The problem that arises is how to utilize solid waste from biomass in the form of wood as fuel when the process of making fried food, the hope is to reduce production operational costs and reduce waste around. The solution given is to use a biomass waste fuel stove, namely wood or charcoal, a stove with a gasification system. The utilization of wood waste and biomass as fuel can be a solution when LPG is scarce or the availability of wood waste is abundant. By calculation, using wood waste for cooking requires approximately 6 kg, economically it is cheaper because it utilizes biomass waste that is around. The disadvantage of using wood waste fuel is regarding the combustion residue, namely ash.